Financial planning training and literacy enhancement for muslim families at Pimpinan Ranting ‘Aisyiyah (PRA) Ngestiharjo, Bantul - Nano Prawoto; Bachtiar Dwi Kurniawan; Asma Munifatussaidah; Fitra Prasapawidya Purna; Adhianty Nurjanah (Community Empowerment, 2025)
This community service program is motivated by the phenomenon of financial literacy, particularly in managing and planning finances within the family realm in the Kasihan District, Bantul Regency, where many individuals experience difficulties managing daily and monthly finances. As a result, many people become trapped in debt due to weak household financial management. The purpose of this community service activity is to improve financial literacy, especially in household financial management, among members of the Ngestiharjo 'Aisyiyah Branch Leadership (PRA) and the surrounding community in Bantul Regency. This program initiative addresses challenges in Kasihan District, including difficulties in managing daily and monthly finances and the rising problems of debt caused by inadequate financial management. Empirical data from a survey of 40 community members at Perum SBI Ngestiharjo, Bantul Regency, highlights the urgency for targeted training. The service employs a participatory seminar method, which directly involves participants in planning, implementing, and evaluating activities. Additionally, the training incorporates the use of a budget planning application and emphasizes financial management that aligns with Islamic values. The results of the community service indicate that the program has achieved its objectives, significantly improving financial literacy and management practices among PRA Ngestiharjo members and the surrounding community. The assessment reveals that the training effectively promotes financial literacy and awareness of Islamic financial management principles among Muslim households. Following the training, the financial literacy of Muslim household participants increased from 36% to 100%.